0128 Prevalence and Characteristics of Dreaming Across Nine Countries, and Associations With Life Stress. (12th April 2019) - Djurich, Sara; Havens, Cody M; Parthasarathy, Sairam; Grandner, Michael A
Abstract: Introduction: Dreams are a hallmark of sleep and can be influenced by social, environmental, and cultural factors. Yet, few studies have examined international variability of dream-related factors. The present study examined dream-related content across nine countries, representing four continents. Methods: Data were obtained from surveys administered to N=7, 312 adults from: the USA(N=1911), France(N=511), Japan(N=750), China(N=1256), Brazil(N=760), South Korea(N=503), Germany(N=527), the United Kingdom(N=572), and the Netherlands (N=522). Participants were asked to evaluate how often they dream, experience recurrent dreams, remember dreams, and if their dreams impact waking activities (i.e., feelings upon awakening, daytime feelings, and sleep difficulties). Life stress over the previous three months was also assessed. All items were asked on a 5-point Likert scale. Multiple ordinal logistic regressions modeled the dream variables as outcomes, with country as a predictor (adjusted for age and sex). To examine if life stress moderated dream-related variables, separate models were also fit to examine the interaction between life stress and country. Results: Compared to the USA, dream frequency was lower in Japan, China, Brazil, South Korea, Germany, UK, and The Netherlands. Recurrent dreams were less common in France, Japan, China, South Korea, Germany, UK, and The Netherlands. Dreams were less frequently remembered in France, Japan, China, South Korea, Germany, UK, and The Netherlands. Perceived impact of dreams was higher in France, China, South Korea, and UK. Impact following waking was less in Japan, Brazil, and The Netherlands, but greater in China. Links between dreams and sleep problems were considered more in China and less in Japan, Brazil, South Korea, Germany, and The Netherlands. Greater life stress was associated with higher levels of all dream variables, though this varied by country. Conclusion: Dreams are experienced differently between countries. Further, the association of life stress and dreaming differs by country. Culturally-influenced perceptions of dreams could affect perceived relationships with stress. Support (If Any)